2021
DOI: 10.3390/met11050825
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Li Distribution in Synthetic Recycling Slag with SIMS

Abstract: The recovery of technically important elements like lithium from slag of pyrometallurgical recycling of lithium traction batteries will be very important in future due to the expected increasing demand of this element with the upcoming world-wide implementation of electro mobility. Therefore, the investigation of possibilities to recover lithium from pyrometallurgical slag from the recycling of lithium traction batteries is mandatory. In this context, the EnAM (engineered artificial mineral) approach is very p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Provided that the phase of interest is lithium aluminate (LiAlO 2 ), the assumption that only Al is present in the element map is used. Despite the thermochemical simulation in Table 3 predicting another Li-Al species (LiAl 5 O 8 ), it is expected that the experimental slag will incorporate LiAlO 2 as the main potential Li-Al species [28].…”
Section: Micro X-ray Fluorescence (µXrf)mentioning
confidence: 98%
See 2 more Smart Citations
“…Provided that the phase of interest is lithium aluminate (LiAlO 2 ), the assumption that only Al is present in the element map is used. Despite the thermochemical simulation in Table 3 predicting another Li-Al species (LiAl 5 O 8 ), it is expected that the experimental slag will incorporate LiAlO 2 as the main potential Li-Al species [28].…”
Section: Micro X-ray Fluorescence (µXrf)mentioning
confidence: 98%
“…Consequently, the thermochemical outcomes may not accurately represent the actual experimental results. Based on prior studies on similar slag systems [8,20,21,27,28], it was observed that only LiAlO 2 , as a Li-Al species, is identified in the experimental slag. It is worth noting that LiAl 5 O 8 , while theoretically plausible, is not found in the system based on these mentioned studies.…”
Section: Thermochemical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The new approach is applied to the oxidic system Li 2 O–SiO 2 since it forms an important subsystem of the multicomponent lithium containing slag that is increasingly generated from Li-ion battery processing industries. Such a slag system has garnered much interest among the scientific community as a potential source for Li recycling. , However, the interplay of complex kinetics influenced by varied process conditions hinders, to some extent, controlled solidification evolution of the melt system of interest or in other words achieving the desired element recovery. Engineering particular crystals out of the slag with a high concentration of the element of interest can only be performed when the internal process kinetics can be understood and tailored according to external process parameters in terms of heat extraction profiles.…”
Section: Introductionmentioning
confidence: 99%